Design & development of a data acquisition system for smart grids - Hamilton, Robert (2015)
The objective of this project is to create an Energy Management System (EMS) with sophisticated functionality to monitor and regulate the power supply in an office building over the course of a typical working day in Singapore. The project aims to build and develop an EMS to integrate a photovoltaic array and electric vehicle (EV) batteries for an office building in Singapore. During periods when the output power of the PV array is lower than the demand requirement of the building, EV batteries will be used to balance the power deficit of the building, a technique commonly known as vehicle-to-grid (V2G) conversion. Conversely, when there is excess power generated from the PV array, the building will receive its power from the solar PV whilst the excess power is used to charge the EV batteries, known as grid-to-vehicle (G2V). Naturally, when sufficient power is available from the PV array to meet the demand of the building, the PV array will be used alone to supply the buildings power. Both conventional analysis techniques and a state-of-the-art programmable solar array was used to obtain the power output from a given PV array over the course of one year in Singapore. This analysis is carried out through the use of real time solar irradiance and temperature data. Data gathered by a weather station at NTU is used to simulate real-life conditions. Additionally an investigation into both time coordinated and power coordinated charging and discharging (TCC/D and PCC/D) of EVs explored the use of three different priority criteria to schedule the EVs at each interval during the working day. Ultimately, data-driven simulations in LabVIEW simulate the behaviour of the PV array and an EMS, capable of adopting various priority criterion based on TCC/D and PCC/D, manages the power by enabling either G2V or V2G power transfer. The EMS provides a platform for analysis of the overall system by bringing together the solar power available in Singapore with an array of EVs on a coordinated charging and discharging scheme.